A novel evaluation approach for functional impairment in subacromial impingement syndrome: focus on Temporal Summation of Activity-related Pain (TSAP) - Tanaka, Katsuyoshi; Oda, Shota; Izumi, Masashi (PeerJ, 2025)
Background Patients with subacromial impingement syndrome (SIS) often experience increased pain during repetitive upper-extremity movements in their daily life. However, conventional assessments of movement-evoked pain are mostly limited to single movement pain (SMP) and may not fully capture the effects of pain during repetitive activities. In this study, we developed the Temporal Summation of Activity-related Pain (TSAP) as a novel method for assessing increases in pain intensity during repetitive movements, and investigated its clinical usefulness. Methods Thirty patients with SIS were included in this cross-sectional study. Movement-evoked pain was assessed using patient-reported outcome measures, SMP and TSAP scores, which were evaluated by the increase in pain intensity after 10 repetitions of a shoulder abduction task. Additionally, the conventional temporal summation of pain (cTSP) was assessed using pinprick stimulation. We analyzed the association between the parameters and the impact of movement-evoked pain on upper extremity dysfunction assessed using Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH). Results The TSAP score significantly correlated with the cTSP and QuickDASH scores (p < 0.05). Regression analyses revealed that the TSAP score was the only significant factor explaining the impact on upper extremity dysfunction, even after controlling for confounding factors [B (95% CI) = 0.461 (0.099–0.824), p = 0.015]. Conclusions TSAP provides valuable insights into the functional impact of pain in patients with SIS. Our findings suggest that TSAP may offer a more sensitive evaluation of movement-evoked pain compared to conventional assessments, although further validation is needed.
Keywords: Subacromial impingement syndrome; Functional impairment; Temporal summation of activity-related pain; Movement-evoked pain